CUSTOMER ATTITUDE THAT INFLUENCES THE LOYALTY CUSTOMER ON STORE DEPARTEMENT IN BATAM - hasan, golan (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This study aims to examine whether there is an influence between overall service quality, relationship strength and relationship quality on customer loyalty in retail companies. The sample of this study is consumers who have visited department stores ( Top 100, JC Supermarket, Golden Truly and Hypermart) in Batam. This study was tested using a sample of 120 respondents. The method used is a survey that is by distributing questionnaires to the samples that have been determined above and analysis tools using regression. This study shows that overall service quality and relationship strength have a significant positive effect on customer loyalty. While relationship quality does not have a significant effect on customer loyalty. Overall service quality is a strategy in marketing that is used to maintain the relationship between customers and the company so that it needs to be fostered properly. good service has long-term benefits that will have a positive impact in the form of profits obtained by the company to face competition. That way the company needs to improve overall service quality to build relationship strength and relationship quality because the existence of a good relationship between consumers and the company will lead to customer loyalty